SOME ORGANOPEROXO COMPLEXES OF ZIRCONIUM (IV), THORIUM (IV) AND URANIUM (VI)
Some new peroxo complexes of Zr (IV), Th (IV) and U (VI) containing organic ligands, L [N4Cl1IlC1I.oH)2); P, [N2CjHs(C6H.oH)J; LID,[(C6I-IjCNC2H4NH)2) and UV, [C6H4 NNH=CHC1I.oH] have been synthesized and char- acterized. These have compositions, [Zr(02)U], [Th(02) U] HP, [U(0)(02) LIT) H20, [U(0)(02) LIT],Zr (02)’ LID], [Th(02)2 I